Coupling states in moving quasi-neutral medium - Agafonov, A.V. (Вопросы атомной науки и техники, 2005)
The possibility of existence of spherically symmetrical quasi-neutral collective coupling states (CCS) in collisionless plasma is discussed. Correlation phenomena in quasi-neutral systems with hot electron component moving with average velocity close to ion one may occur in greatest degree and guide to the advantage of CCS forming. CCS consists of large numbers of electrons and ions, and represent regions with the potential differing from average (zero) plasma potential. The concept of CCS can be considered as non-linear BGK-waves. This definition is just applied in great degree for equilibrium configurations with non-linear electrostatic field. The simplest spherically symmetrical configuration has been considered without spin and polarisation in the frame of kinetic description for monochromatic on energy electron and ion components and distribution functions on full momentum in forms of simple power functions of different powers for electrons and ions. Asymptotic analytical and full numerical solutions were found for CCS with captured and passing particles turning into final density neutral plasma created chaotically moving electrons and ions in rest. Обговорюється можливість існування сферично симетричних квазінейтральних колективних зв'язаних станів (КЗС) у беззіштовхувальній плазмі. У квазінейтральних системах, утворених гарячим електронним компонентом, що рухається із середньою швидкістю близької до швидкості іонів, істотно виражені кореляційні явища, що обумовлюють формування КЗС. КЗС утворюються великим числом електронів і іонів і являють собою області з потенціалом, що відрізняється від середнього (нульового) потенціалу плазми. КЗС можна розглядати також як нелінійні БГК-хвилі. Останнє визначення саме в більшому ступені використовується для опису рівноважних станів з нелінійними електростатичними полями. Як приклад у рамках кінетичного опису, у якому електрони й іони є монохроматичними по енергії, а розподіли по моментах обрані у виді простих степеневих функцій з різними показниками для електронів і іонів, розглянуті найпростіші сферично симетричні конфігурації, що не мають спин і поляризацію. Отримано аналітичні асимптотичні і повні чисельні рішення, що описують КЗС із захопленими і минаючими частками, що переходять у нейтральну плазму кінцевої густини, утворену електронами, що хаотично рухаються, і непорушними іонами. Обсуждается возможность существования сферически симметричных квазинейтральных коллективных связанных состояний (КСС) в бесстолкновительной плазме. В квазинейтральных системах, образованных горячей электронной компонентой, движущейся со средней скоростью близкой к скорости ионов, существенно выражены корреляционные явления, обуславливающие формирование КСС. КСС образуются большим числом электронов и ионов и представляют собой области с потенциалом, отличающимся от среднего (нулевого) потенциала плазмы. КСС можно рассматривать также как нелинейные БГК-волны. Последнее определение как раз в большей степени используется для описания равновесных состояний с нелинейными электростатическими полями. В качестве примера в рамках кинетического описания, в котором электроны и ионы монохроматичны по энергии, а распределения по моментам выбраны в виде простых степенных функций с различными показателями для электронов и ионов, рассмотрены простейшие сферически симметричные конфигурации, не обладающие спином и поляризацией. Получены аналитические асимптотические и полные численные решения, описывающие КСС с захваченными и проходящими частицами, переходящими в нейтральную плазму конечной плотности, образованную хаотически движущимися электронами и покоящимися ионами.